Landslide Processes Involved in Volcano Dismantling From Past to Present: The Remarkable Open‐Air Laboratory of the Cirque de Salazie (Reunion Island). Issue 5 (21st May 2022) - Rault, C.; Thiery, Y.; Chaput, M.; Reninger, P. A.; Dewez, T. J. B.; Michon, L.; Samyn, K.; Aunay, B.
Abstract: The Cirque de Salazie is one of the large erosional depressions of Reunion Island. Composed of a thick accumulation of loose volcaniclastic materials derived from successive volcanic flank collapses and exposed to high precipitation rates, this large depression is particularly prone to landslides. Of the 133 km 2 making up this large depression, at least 19% of slopes are affected by various types of landslides. The diversity and high density of landslides is one of the main issues for inhabited areas. We examine the landslides in this area with the goal of providing key elements for better hazard assessment and understanding their role in the landscape's evolution. For over 20 years, we have been acquiring multidisciplinary data on landslides. In this cirque, eight types of landslides are identified and described following an adapted landslide classification. Using a multidisciplinary approach, we characterize and interpret the surface morphology and internal structure of three large inhabited compound landslides with volumes of 0.1 km 3 moving up to 1.15 myr −1 . These complex landslides provide an opportunity to investigate the influence of past slope movements on current slope movements. Furthermore, using detailed mapping and volume calculation of the landslides triggered by the last major cyclonic rainstorm, we estimate that rainfall‐triggered landslides contribute up to 20% of the long‐term erosion rate. The Cirque de Salazie is a remarkable laboratory that offers new insights and challenges for future research on landslide hazard assessment and the role of landslides in the short‐ and long‐term dismantling of volcanoes. Plain Language Summary: An exceptional diversity and density of landslides is observed in the Cirque de Salazie (Reunion Island). Whatever their type (slow‐moving to sudden landslides), they all cause significant damage to buildings and infrastructure. They also contribute to the dismantling of the island at longer time scales. We have collected multiple types of data on these landslides over 20 years in order to understand their dynamics and eventually improve the related hazard assessment. These data allow us to define and characterize eight landslide types that are all controlled by the hydrometeorological conditions of the cirque, making Salazie an ideal laboratory to study the erosion‐related interactions. Key Points: The high density and diversity of landslide processes observed in the Cirque de Salazie make it an ideal laboratory Large compound landslides carry indications of past volcanic debris‐avalanches but also of local paleo‐stress fields Cyclonic rainstorm landslides contribute to the long‐term erosion of the volcanic edifice